Dampak Tingkat Pendidikan terhadap Kemiskinan di Sumatera Utara Tahun 2017-2021 - Rey Septanislaus Togatorop; Maysri Handayani Putri Sinaga; Nazwa Aulia Putri; Roihanah Hafifah; Azra Lena Nuraina (Jurnal Simki Economic, 2024)
This research aims to investigate the relationship between education level and poverty level in North Sumatra during the 2017-2021 period. The data used was sourced from the Central Statistics Agency (BPS) and analyzed using the linear regression method via the Statistical Package for the Social Sciences (SPSS) software. The research sample includes secondary data that records education levels and poverty levels in North Sumatra. The results of the analysis show that there is a significant relationship between the level of education and the level of poverty in the region.